ANALISIS GAYA KEPEMIMPINAN DAN KINERJA KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMA SWASTA TARUNA HANG TUAH TELUKDALAM KECAMATAN TELUK DALAM KABUPATEN NIAS SELATAN - KARTIKA, ELYARONA; SILABAN, PASAMAN; HUTAHAEAN, MARLAN (LP2MTBM MAKARIOZ, 2021)
The scope of this study aims to analyze the Leadership Style and Performance of the Principal in Improving Teacher Performance in Hang Tuah Private High School, Teluk Dalam District, South Nias. This type of research is a qualitative research and the location studied is in Private Hang Tuah, Teluk Dalam District, South Nias. This research is a qualitative research. Data collection procedures used in this study are observation, interviews, and documentation. The results of this study indicate that the leadership style of the Headmaster of SMA Taruna Hang Tuah Telukdalam has a democratic leadership style and good performance in improving teacher performance. This leadership style can be seen from the leadership characteristics of the Headmaster of SMA Taruna Hang Tuah Telukdalam including: shared workload, willingness to accept opinions, criticism and suggestions, involving subordinates in decision making, trusting subordinates by continuing to supervise, two-way communication and prioritizing common interests. In addition, the principal's performance. The principal's performance is the ability to carry out the work or tasks that are owned in completing a job at the school he leads.